Exploring flipped learning - Abd Rahman, Siti Fatimah; Embi, Mohammed Amin; Md Yunus, Melor (School of Educational Studies, Universiti Sains Malaysia, 2017)
Pedagogical changes and adaptation of new models in teaching and learning should be considered as a great effort to a better nation. One of the most popular growing models in Malaysia is flipped learning. Flipped learning is widely used all over the world in teaching and learning of different fields of subjects. It promotes meaningful learning, more to student-centered rather than teacher-centered, and commonly aided with technological equipment such as pre-recorded videos, mobile apps or simply watching videos on YouTube before coming to the class. This article explores the characteristics of the flipped learning, the overview from the previous research, as well as teachers and students roles in implementing flipped learning. The advantages and disadvantages of flipped learning are also highlighted and discussed for further understanding of this model. Before it ends with a conclusion, the implications of teaching and learning are also discussed.